Risk factors for hydroxychloroquine retinopathy in systemic lupus erythematosus: a case–control study with hydroxychloroquine blood-level analysis. (23rd May 2020) - Lenfant, Tiphaine; Salah, Sawsen; Leroux, Gaëlle; Bousquet, Elodie; Le Guern, Véronique; Chasset, François; Francès, Camille; Morel, Nathalie; Chezel, Julie; Papo, Thomas; Cacoub, Patrice; Mouthon, Luc; et al.
Abstract: Objective: HCQ is an essential medication in SLE, proven to lengthen survival and reduce flares. Its use, however, is limited by its rare but severe ophthalmological complications. Here, we aimed to analyse factors associated with HCQ retinopathy including HCQ blood levels. Methods: This case–control study compared SLE patients with and without HCQ retinopathy, defined by abnormal results for at least two of the following ophthalmological tests: automated visual fields, spectral-domain optical coherence tomography (SD-OCT), multifocal electroretinogram (mfERG) and fundus autofluorescence. We compared clinical and laboratory findings to assess risk factors for HCQ retinopathy. Results: The study included 23 patients with confirmed retinopathy (cases) and 547 controls. In the univariate analysis, age ( P < 0.001), height ( P = 0.045), creatinine clearance ( P < 0.001), haemoglobin concentration ( P = 0.01), duration of HCQ intake, ( P < 0.001), higher cumulative HCQ dose ( P < 0.001) and geographical origin (West Indies and sub-Saharan Africa) ( P = 0.007) were associated with the risk of retinopathy, while HCQ blood levels were not. In the multivariate analysis, only cumulative dose ( P = 0.016), duration of intake ( P = 0.039), creatinine clearance ( P = 0.002) and geographical origin ( P < 0.0001, odds ratio 8.7) remained significantly associated with retinopathy. Conclusion: SLE patients on HCQ should be closely monitored for retinopathy, especially those from the West Indies or sub-Saharan Africa, or with renal insufficiency, longer HCQ intake or a high cumulative dose. Although reducing the daily dose of HCQ in patients with persistently high HCQ blood levels seems logical, these concentrations were not associated with retinopathy in this study with controls adherent to treatment.